Truncations in word forming and syntactical nomination - Купрікова, Галина Віталіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
In the article the classification of truncations in modern linguistics is described. The basic models of forming truncated names are analyzed. Truncation is a special way of word formation that is shortening by deleting parts of the word stem (suffixes, prefixes, roots, syllables, elements of a compound word). Truncation of syntactic structures demonstrates language economy; truncation is widespread in colloquial language, jargons. Secondary nomens, which are motivated by full names, are identical in meaning (or just differ by stylistic coloring), but they are different in form.